2021
DOI: 10.1001/jamaneurol.2020.3627
|View full text |Cite|
|
Sign up to set email alerts
|

A 5-Decade Analysis of Incidence Trends of Ischemic Stroke After Transient Ischemic Attack

Abstract: IMPORTANCE Management of transient ischemic attack (TIA) has gained significant attention during the past 25 years after several landmark studies indicated the high incidence of a subsequent stroke.OBJECTIVE To calculate the pooled event rate of subsequent ischemic stroke within 2, 7, 30, and 90 days of a TIA and compare this incidence among the population with TIA recruited before 1999 (group A), from 1999 to 2007 (group B), and after 2007 (group C).DATA SOURCES All published studies of TIA outcomes were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 109 publications
(312 reference statements)
2
43
1
Order By: Relevance
“…Transient ischemic attack and minor stroke (TIAMS) account for up to 58% of all cerebral ischemic events ( 1 , 2 ). Although recurrent vascular event rates post-TIAMS have been declining over the past two decades ( 3 , 4 ), 5–8% of patients have disabling stroke, 1.1–1.3% have coronary artery events, and 0.6–0.7% die from cardiovascular causes in the year following TIAMS ( 5 7 ). Short-term dual antiplatelet therapy (DAPT) is the current gold standard for secondary prevention in high-risk TIAMS patients with non-cardioembolic sources ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transient ischemic attack and minor stroke (TIAMS) account for up to 58% of all cerebral ischemic events ( 1 , 2 ). Although recurrent vascular event rates post-TIAMS have been declining over the past two decades ( 3 , 4 ), 5–8% of patients have disabling stroke, 1.1–1.3% have coronary artery events, and 0.6–0.7% die from cardiovascular causes in the year following TIAMS ( 5 7 ). Short-term dual antiplatelet therapy (DAPT) is the current gold standard for secondary prevention in high-risk TIAMS patients with non-cardioembolic sources ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…There was substantial heterogeneity between studies. Furthermore, in a most recent systematic review and meta-analysis of 206,455 patients in 68 unique studies during 5 decades, the subsequent risk of ischemic stroke was 4.7% within 90 days and the incidence was gradually decreased by the time of trials, among the study population recruited before 1999 was significantly higher ( 25 ). Second of all, the definition of stroke recurrence varies between studies, resulting in different incidences of observed stroke recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, previous reports of stroke risk after TIA is highest in the first 7 days and in patients without immediate treatment (11.0%; 95% CI, 8.6-13.5%) (24). Over the past two decades, new treatment strategies and early management of TIA and minor strokes have significantly reduced stroke recurrence rates (25). The lowest risks were seen in studies of emergency treatment in specialist stroke services [0.9% (95% CI, 0.0-1.9)] (26)(27)(28)(29) and the highest risks in population-based studies without urgent treatment [11.0% (8.6-13.5)] (30)(31)(32).…”
Section: Nbp Compliance and Stroke Recurrencementioning
confidence: 99%
“…The 7-day risk of stroke was higher on DWI-positive than DWI-negative patients (1.2% versus 12.3%) [13]. The subsequent risk of ischemic stroke after TIA was 2.4% in 2 days, 3.8% in 7 days, 4.1% in 30 days, and 4.7% in 90 days according to a systematic review and meta-analysis of 206455 unique patients [19]. It is reasonable to assume higher rates of subsequent ischemic stroke in 30 or 90 days in the TSI population.…”
Section: Discussionmentioning
confidence: 99%